Assessment Of Community Health Centers of Belagavi District According to Indian Public Health Standards 2012 Guidelines: A Cross Sectional Study - Shrinivas K Patil; Shivaswamy MS (Medsci Publications, 2016)
Introduction: The Community Health Centres (CHCs) are under constant criticism for their inability to deliver quality services. National Rural Health Mission (NRHM) has provided the opportunities to develop Indian Public Health Standards (IPHS) in 2005. Objective: To assess Community Health Centres of Belagavi District according to Indian Public Health Standards 2012 guidelines. Methodology: A facility based cross-sectional study was conducted in Belagavi District of Karnataka. Ten CHCs, one CHC from each of the 10 Talukas of Belagavi district were selected by simple random sampling (out of 17 CHCs). Results: In the present study, only 60% of CHCs covered the population as per the norms. All the CHCs had the General Duty Officers,nursing staff, pharmacist and laboratory technician. 40% of CHCs had OBG specialists, 30% had paediatricians, 20% had anaesthetists. All the CHCs had 50-75% of the equipments and drugs and more than 75% of the furniture as per the IPHS norms. Minor surgeries were performed in all the CHCs. Only tubectomy and vasectomy were performed in 50% of CHCs. Obstetric and gynaecological operations were performed in 40% of CHCs. Conclusion: IPHS guidelines are not fully being followed at CHC level in the district. Recruitment of Specialists should be augmented as per the norms.